Break Even Point Analysis at Polibatam Store: Break Event Point - Nova Sabrina (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to evaluate the profitability, fixed costs, variable costs, and break-even point of the Polibatam Store selling clothing and accessories or merchandise. This research uses an analytical method by collecting financial data related to fixed costs, variable costs, and revenue. This research uses primary data. Meanwhile, price and sales data relevant to Polibatam Store. Based on the results of this study entitled Break Even Point Analysis at Polibatam Store, it can be concluded that Polibatam Store has determined the break-even point of Polibatam Store products. Polibatam Store sets a profit target of 40% and with a quantity of 370 units. The total capital for this category is Rp16,900,000 with sales revenue of Rp23,500,000 which results in a profit of Rp6,600,000. While the accessories or merchandise category includes totebags, notebooks, headscarves, brooches, and so on with total sales of Rp9,180,000 resulting in a profit of Rp2,620,000. But after doing the calculations, the researcher found that to break even, namely with income and expenses, Polibatam Store needs to add as many as 24 units. This research provides a comprehensive overview of the profitability, cost, and break-even analysis of the clothing and accessories sales business, as well as the time required to recover the initial business capital.